Precision Medicine: An Optimal Approach to Patient Care in Renal Cell Carcinoma - Sharma, Revati; Kannourakis, George; Prithviraj, Prashanth; Ahmed, Nuzhat (Frontiers in Medicine, 2022)
Abstract Renal Cell Cancer (RCC) is a heterogeneous tumor that shows both intra- and inter-heterogeneity. The heterogeneity is displayed not only in different patients but also between the RCC cells within the same tumor, which makes treatment difficult due to varying degree of responses generated in RCC heterogeneous RCC tumor cells even with the targeted treatment. In that context, precision medicine (PM), in terms of individualized treatment catered for a specific patient or groups of patients, can shift the paradigm of treatment in the clinical management of RCC. Recent progress in the biochemical, molecular, and histological characteristics of RCC has thrown light on many de-regulated pathways involved in the pathogenesis of RCC. As PM-based therapies are rapidly evolving and few are already in current clinical practice in oncology, one can expect that PM will expand its way towards the robust treatment of RCC patients. This article provides a comprehensive background on the recent strategies and breakthroughs of PM in oncology and provides an overview of potential applicability of PM in RCC. The article also highlights on the drawbacks of PM and provides a holistic approach to the care of cancer patients that goes beyond the involvement of clinicians and scientists and encompasses appropriate legislative and administrative care imparted by the healthcare system and the insurance providers. It is anticipated that the combined efforts from all sectors involved will make PM accessible to RCC and other cancer patients making a tremendous positive leap on individualized treatment strategies. This will subsequently enhance the quality of life in patients.